PENERAPAN MODEL PEMBELAJARAN EVERYONE IS A TEACHER UNTUK MENGGALI POTENSI DIRI DAN MENINGKATKAN KETERAMPILAN SISWA KELAS V UPTD SD NEGERI 122384 JL. KOL PEMATANGSIANTAR PADA PEMBELAJARAN BAHASA INDONESIA MATERI CERPEN - Simanjuntak, Melvin; Jojor Parisma Simangunsong; Cristya Febrina Purba; Elfryani Sinaga; Putri Artha Ulina; Selfrina Sipayung; Fransisko Timoti Siallagan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research aims to reveal the effectiveness of implementing the Everyone is a Teacher learning model in exploring personal potential and improving the skills of class V students in learning Indonesian at UPTD SD Negeri 122384 Pematangsiantar. The Everyone is a Teacher learning model was chosen because it gives every student the opportunity to act as a teacher, so it is hoped that it can improve students' skills, self-confidence and communication abilities. This research uses the classroom action research (PTK) method with two cycles. Data collection is carried out through observation and tests. With teaching materials in the form of a short story with the title There are butterflies, there are guests with the synopsis that the character